The Study of Water Content on the Coal Loading Performance of Thin Coal Seam Shearer Drum by Discrete Element Method (DEM) - Kuidong Gao; Wenhe Zhang; Yuanjin Zhang; Weipeng Xu; Liqing Sun (Engineering Reports)
ABSTRACT As the main component of thin coal seam shearers, the drum bears the functions of loading and cutting, and its performance has become an important factor restricting mining efficiency and production safety. In response to the problem of low efficiency in installing thin coal seam shearers, this paper uses the Discrete Element Method (DEM) to study the effects of loading methods, helical angle of drum, drum rotation speed, and particle water content on coal loading rate. Research has found that the coal loading performance of the ejection loading method is much higher than that of the pushing loading method. As the helical angle increases, the average loading rate increases. As the rotation speed increases, the loading rate of wet coal particles gradually decreases. During production and thin coal seam mining, special attentions should be paid to the control of helical angle of drum and drum rotation speed. This study has guiding importance for improving the efficiency of thin coal seam mining.